PsycEXTRA Dataset 2012
DOI: 10.1037/e644632012-001
|View full text |Cite
|
Sign up to set email alerts
|

African American Experiences of Race Relations in the Supervision Dyad

Abstract: Thank you God! Thank you God for the opportunity to shine and to successfully reach a major milestone in my personal and professional life. Thank you God that the doctoral journey is finally over. I also thank you God for bringing champions into my life that have supported me along the way. I'd like to acknowledge those champions. First, my husband, Joe "stud" Johnson. You are my friend and my partner. You truly inspire me. Your sense of humor, smile, encouragement, tough love when I want to slack off, underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…The participants also reported taking on the role as mentors in addition to being a clinical supervisor and noted that in their supervision meetings, they discussed race more often with their Black supervisees than with other supervisees (Goode-Cross, 2011). These findings are further supported by a qualitative study that investigated the lived experiences of ten Black counselors’ experiences as both supervisees and supervisors, working mostly in UCCs, that found that Black supervisees felt more comfortable, supported, understood, and engaged with a Black supervisor (Pritchett-Johnson, 2011).…”
Section: Representation and Mentorship For Woc And Traineesmentioning
confidence: 64%
See 3 more Smart Citations
“…The participants also reported taking on the role as mentors in addition to being a clinical supervisor and noted that in their supervision meetings, they discussed race more often with their Black supervisees than with other supervisees (Goode-Cross, 2011). These findings are further supported by a qualitative study that investigated the lived experiences of ten Black counselors’ experiences as both supervisees and supervisors, working mostly in UCCs, that found that Black supervisees felt more comfortable, supported, understood, and engaged with a Black supervisor (Pritchett-Johnson, 2011).…”
Section: Representation and Mentorship For Woc And Traineesmentioning
confidence: 64%
“…In addition, White supervisors should not be afraid to support their supervisees of color in exploring how their own identities may impact their work with clients and how to advocate for oneself in a predominantly White field (Ancis & Marshall, 2010; Jang et al, 2020). Above all, White supervisors should engage in these conversations with respect, genuineness, and humility, as Pritchett-Johnson (2011) found that Black supervisees reported hypervigilance to their White supervisors’ non-verbal communication and subtle utterances that provide insight into their supervisors’ multicultural awareness. Specifically, White supervisors are responsible for initiating and engaging their supervisees in conversations regarding culture and systems of oppression as it relates to the supervisor’s experiences, the supervisee’s experiences, and the client’s experiences (Ancis & Marshall, 2010; Chan et al, 2015; C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations